SIMULATION OF LANDMARK APPROACH FOR WALL FOLLOWING ALGORITHM ON FIRE-FIGHTING ROBOT USING V-REP - Sumarsih Condroayu Purbarani; Qurrotin A’yunina; Muhammad Anwar Ma’sum; Muhammad Febrian Rachmadi (Faculty of Computer Science - Universitas Indonesia, 2015)
Autonomous mobile robot has been implemented to assist humans in their daily activity. Autonomous robots have also contributed significantly in human safety. Autonomous mobile robot have been implemented to assist humans in their daily activity. Autonomous robots Have also contributed significantly in human safety. An example of the autonomous robot in the human safety sector is the fire fighting robot, which is the main topic of this paper. As an autonomous robot, the fire fighting robot needs a robust navigation ability to execute a given task in the shortest time interval. Wall-following algorithm is one of several navigating algorithm that simplifies this autonomous navigation problem. As a contribution, we propose two methods that could be combined to make the existing wall-following algorithm more robust. The combined wall-flowing algorithm will be compared to the original wall-following algorithm. By doing so, we could determine which method has more impact on the robot’s navigation robustness. Our goal is to see which method is more effective when combined with the wall-following algorithm.